The dynamics of the Vachellia xanthophloea and Faidberbia albida woodlands in the floodplains of the Makuleke Contractual Park - Turner, Jonathan (My University, 2021)
The Makuleke Contractual Park in the far north of the Kruger National Park has a hot, arid climate historically supplemented by variable flooding of the floodplains of the Limpopo and Luvuvhu Rivers. The floodplains form the Makuleke Ramsar Wetlands with diverse vegetation including beautiful monospecific Vachellia xanthophloea and Faidherbia albida woodlands. A landscape level study examined the dynamics of these woodlands in the chronological order of different phases of establishment, decline and regeneration, and how they were affected by various ecological drivers over a period of half a century. Use was made of aerial photographs, Google Earth imagery and ground survey methods to track woodland changes. Episodic events were key drivers of the woodland dynamics. Anthropogenic factors, geology and soils, climate and hydrology, elephants, mesobrowsers and senescence all played roles. The Makuleke people lived in the area until they were forcibly removed in 1969, when the area was incorporated into the Kruger National Park. With their departure, and farming activities terminated, the anthropogenic influence shifted to one governed by the conservation policies of the Kruger National Park. This created a changed environment under which most of the woodlands established. The abiotic template of climate, geology and soils is presented. The average annual rainfall was 437 mm but with a high coefficient of variation. Infrequent flooding of the floodplains from the Limpopo and Luvuvhu Rivers introduced hydrological variability and two large infrequent flood disturbances occurred, dramatically affecting the morphology of the Luvuvhu River and dynamics of the woodlands. How the hydrological regime, large flood disturbances, geology and soils have determined the spatio-temporal distribution of the woodlands in the floodplain is discussed. Under the hot, arid climate premature stress induced senescence in the V. xanthophloea woodlands occurred. The Makuleke elephant population increased from a very low base and exerted an increasing impact on all the phases of the woodlands. Elephants were shown to be the major cause of the decline of the V. xanthophloea woodlands but not the F. albida woodlands. The spatial distribution of the areas of regeneration of both woodland species was shown to be influenced by soil form in the floodplains. The role of mesobrowsers, especially impalas, in constraining, and in some cases terminating, regeneration at seedling stage is covered. The concept of a “browse trap” created by mesobrowsers and elephants for both the seedling and sapling stages in the regeneration phase of the woodlands was demonstrated. The area of regeneration was not replacing the area of woodland lost, and reasons are given. The conclusion highlights the unique characteristics of, and differences between, the two woodland species and how the roles of the key ecological drivers differed in their influence on the dynamics of each of the two woodlands. Their likely influence on the future of the woodlands is discussed. In particular, an increasing elephant population and possible changing flood regime are likely to have major impacts. Recommendations are made for further research that should benefit conservation management of the Makuleke Ramsar Wetlands
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science, 2021